(untitled) (Sudurpaschim Spectrum, 2024)
This paper presents a psychoanalytic reading of Haruki Murakami’s Colorless Tsukuru Tazaki and His Years of Pilgrimage, focusing on the protagonist Tsukuru Tazaki’s psychological journey through themes of repression, trauma, and identity formation. Drawing on Sigmund Freud’s theories of repression, the uncanny, and the dynamics between the id, ego, and superego, the study examines how Tsukuru’s unresolved trauma manifests in recurring dreams, fragmented relationships, and his perception of himself as “colorless.” Prompted by Sara, a pivotal figure who acts as a guide and mirror to his unconscious fears, Tsukuru embarks on a pilgrimage to confront his estranged friends and uncover the truth behind their rejection. Through close textual analysis of key symbols—such as train, color imagery, music, and liminal spaces—the paper reveals how repressed memories resurface as Tsukuru grapples with betrayal, grief, and the fragility of human connections. While Tsukuru ultimately uncovers hidden truths about his past, his journey toward emotional healing remains incomplete, underscoring the cyclical nature of repression and the unconscious mind’s persistent influence. Murakami’s novel portrays the delicate interplay between conscious and unconscious forces, emphasizing the enduring challenges of reconciling with one’s past and forging meaningful connections amidst the ambiguities of human existence.